Effective treatment of complex statical and dynamical load combinations within shakedown analysis of 3D frames. (1st October 2015) - Leonetti, Leonardo; Casciaro, Raffaele; Garcea, Giovanni
Highlights: Shakedown analysis of 3D frames subjected to complex load combinations is presented. The strategy is suitable to treat n -dimensional load space ( n of order of hundred). The algorithm avoids redundant constraints improving computational performances. The method deals with seismic actions coming from response spectrum analysis. Abstract: A strategy for an efficient treatment of load combinations is proposed with the aim of making the shakedown analysis an affordable design tool to be used in practical applications. The paper refers to 3D frames subjected to complex combinations of statical and dynamical loads defined according to Eurocode rules. The yield surface of the sections is defined by its support function values associated to presso-flexural mechanisms and it is approximated as Minkowski sum of ellipsoids. An algorithm capable of detecting the significant vertexes of the elastic envelope and suitable for use in the case of response spectrum analyses, is proposed.